Capital structure and size: new evidence across the broad spectrum of SMEs. Issue 12 (1st December 2014) - M. Hull, Robert; Daskalakis, Nikolaos; Eriotis, Nikolaos; Thanou, Eleni; Vasiliou, Dimitrios
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to add to the existing literature by examining a number of hypotheses relating to the capital structure decision in relation to the firms' size, namely by distinguishing among micro, small and medium firms. Design/methodology/approach – The paper examines the hypothesis that the factors determining capital structure are different for firms belonging to different size groups. The authors use a panel data model capturing the dynamic concept of capital structure. Findings – The authors find that whereas the size of the firm does affect how much debt a firm will issue, it does not influence the relationship between the other regressors and debt usage. Research limitations/implications – The paper examines the small and medium enterprises (SMEs). Does not examine the large firms. Practical implications – During the last decade there has been a gradually increasing interest shown in the field of SMEs. These enterprises represent important parts of all economies in terms of both their total number and their job offer and job creation. For example, in the European Union (EU), in 2005, SMEs accounted for 99.8 percent of the total number of enterprises operating in EU-27, covering 66.7 of total employment in the non-financial business economy sector. Social implications – This paper relates capital structure decision to firms' size distinguishing them among micro, small and medium firms. Originality/value – The paper tests differences in capital structure determination among different size groups of enterprises in a dynamic framework for more than one year.